Fundamentals of fluid-solid interactions : analytical and computational approaches - Wang, Xiaodong Sheldon (Monograph series on nonlinear science and complexity, 2008)
This book focuses on the computational and theoretical approaches to the coupling of fluid mechanics and solids mechanics.In particular, nonlinear dynamical systems are introduced to the handling of complex fluid-solid interaction systems, For the past few decades, many terminologies have been introduced to this field, namely, flow-induced.